Approach of Self-Control Therapy Based on The Arabic Terms of ‘Maqasid Syariah’ Towards the Views of Malaysian Students Falling in Love and Having Suicidal Thoughts - Mohd Sham, Kamis; Muhammad Nazir, Alias; Muhd Syahazizamir, Sahmat; Siti Nasuha, Singki; Luqman Hakim, Satiman; Amalia, Madihie; Fatin Ardani, Zamri (2022)
This article aimed to investigate three (3) objectives, there were five (5) participants involved in present study. The qualitative approach employed by the researchers for the present study via interview protocols. The finding indicated that in ‘Finding 1’ that most individuals preferred that family and friends are closer than anyone else. This relationship could allow seeking help for their problem. Participants 2, 3 and 4 revealed suicides will bring sadness to beloved families. These preferences indicated that family or somebody closer influenced daily life. Lastly, regarding ‘Finding 3’ this finding is that love is also considered a big factor in connecting either family or close friends to seek guidance or advice from suicide or negative attitude. The present study encourages that the individuals’ relationship such as relationship factors such as, beloved family and friends around us influence as control- self therapy to avoid suicidal thoughts from appearing among individuals. A few of them, prefer the religious belief as other factors that influenced them in this kind of situation. Therefore, suicide prevention begins with identifying the notice symptoms and bringing them enormously to a doctor or a psychologist.